Non-Linear and Linear System Identification of Debutanizer Column - Md Radzi, Mohamad Razlan (Universiti Teknologi PETRONAS, 2014)
Debutanizer column is one of the common unit operation in a chemical industry. The column is complex and unpredictable in nature, making them difficult to be handled. Hence, system identification is used in identifying and estimate mathematical models of dynamic systems of the debutanizer column from measured data. The identification was done to achieve stability of the debutanizer column through simulation through obtaining linear and non-linear process models using System Identification Toolbox. In this simulation, process model or polynomial model tool will be used to identify linear system and as for nonlinear system, nonlinear model tool is the tool of choice. Based on results obtained from linear system identification, the system is unstable under linear condition. As for nonlinear system identification, the system is stable at certain parameter and unstable at the rest. Further work needs to be done to improve the result.